Development of the Inkit Application Using the Flipped Classroom Model to Enhance Self-Directed Learning and Student Achievement in Economics - Arini Aryanti; Ali Muhson (International Journal of Social Sciences, Language, and Education, 2026)
This study aimed to develop the INKIT application integrated with the flipped classroom model and examine its feasibility, practicality, and effectiveness in enhancing students’ self directed learning and learning achievement in economics education. The research employed a Research and Development approach using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The participants involved 71 eleventh grade students of SMA Negeri 9 Tasikmalaya divided into experimental and control groups through purposive sampling. Data were collected using validation sheets, observations, interviews, questionnaires, and pretest posttest assessments. The findings indicated that the application achieved feasible criteria based on material expert validation of 79 percent and media expert validation of 75 percent. Practicality testing also showed highly positive responses from teachers and students. Inferential statistical analysis revealed significant differences between the experimental and control groups, with a Partial Eta Squared value of 0.559 indicating substantial effectiveness. The N Gain results demonstrated moderate improvement in self directed learning and learning achievement among students using the INKIT application integrated with flipped classroom learning.